Net zero in power and industry—creating or destroying value and jobs? - Caroline Ganzer; Piera Patrizio; Niall Mac Dowell (iScience)
Summary: Value and job creation are frequently claimed as positive by-products of decarbonization. The lack of a standardized methodology and quantitative analyses limit the credibility of such claims. In this work we apply the Jobs and Economic Development Impacts (JEDI) framework to our model of UK power and industry and consistently quantify the impact on economic value and employment for a range of net zero scenarios. Our results suggest that a net zero target can create gross value added and jobs under the right conditions. Offshoring industrial emissions, however, results in a reduction of both, whereas expanding domestic low-carbon industry can lead to further value and job creation. We determine economic sectors with gains and losses, and quantify the impact of local supply chains vs. importing goods and services. A thought experiment indicates ways to further increase value added.